An operational definition of primary refractory acute myeloid leukemia allowing early identification of patients who may benefit from allogeneic stem cell transplantation - Ferguson, P; Hills, R; Grech, A; Betteridge, S; Kjeldsen, L; Dennis, M; Vyas, P; Goldstone, A; Milligan, D; Clark, R; Russell, N; Craddock, C (Ferrata Storti Foundation, 2016)
Up to 30% of adults with acute myeloid leukemia fail to achieve a complete remission after induction chemotherapy - termed primary refractory acute myeloid leukemia. There is no universally agreed definition of primary refractory disease, nor have the optimal treatment modalities been defined. We studied 8907 patients with newly diagnosed acute myeloid leukemia, and examined outcomes in patients with refractory disease defined using differing criteria which have previously been proposed. These included failure to achieve complete remission after one cycle of induction chemotherapy (RES), less than a 50% reduction in blast numbers with >15% residual blasts after one cycle of induction chemotherapy (REF1) and failure to achieve complete remission after two courses of induction chemotherapy (REF2). 5-year overall survival was decreased in patients fulfilling any criteria for refractory disease, compared with patients achieving a complete remission after one cycle of induction chemotherapy: 9% and 8% in patients with REF1 and REF2 versus 40% (P<0.0001). Allogeneic stem cell transplantation improved survival in the REF1 (HR 0.58 (0.46-0.74), P=0.00001) and REF2 (HR 0.55 (0.41-0.74), P=0.0001) cohorts. The utilization of REF1 criteria permits the early identification of patients whose outcome after one course of induction chemotherapy is very poor, and informs a novel definition of primary refractory acute myeloid leukemia. Furthermore, these data demonstrate that allogeneic stem cell transplantation represents an effective therapeutic modality in selected patients with primary refractory acute myeloid leukemia.